MAKING AN ECOLOGICAL TRAP: Capturing the Potentiality of iPS Cells in Japan. - Wakana Suzuki (Social Analysis, 2022)
Inspired by recent discussions of 'traps' among STS and anthropology scholars, this article explores how Japanese scientists capture iPS (induced pluripotent stem) cells to take advantage of their potentialities. Since iPS cells are tiny, unstable, and permeable, humans cannot intervene directly to transform their morphology and nature. Making a proper environment for their thriving--in other words, creating a trap--is the only way for humans to successfully harness and direct the cells' potentiality. Based on long-term fieldwork in one laboratory, I suggest that the technologies, institutions, and laws that mediate between humans and cells can be understood as a series of 'ecological traps'. Ultimately, iPS cells resist unilateral standardization and commercialization, forcing humans to adapt their own behaviors and governing systems to accommodate cells.